Simultaneous implant placement with autogenous onlay bone grafts: a systematic review and meta-analysis - Guoqiang Ma; Chaoan Wu; Miaoting Shao (SpringerOpen, 2021)
Abstract Several authors have suggested that implants can be placed simultaneously with onlay bone grafts without affecting outcomes. Therefore, the purpose of this study was to answer the following clinical questions: (1) What are the outcomes of implants placed simultaneously with autogenous onlay bone grafts? And (2) is there a difference in outcomes between simultaneous vs delayed placement of implants with autogenous onlay bone grafts? Databases of PubMed, Embase, and Google Scholar were searched up to 15 November 2020. Data on implant survival was extracted from all the included studies (single arm and comparative) to calculate point estimates with 95% confidence intervals (CI) and pooled using the DerSimonian-Laird meta-analysis model. We also compared implant survival rates between the simultaneous and delayed placement of implants with data from comparative studies. Nineteen studies were included. Five of them compared simultaneous and delayed placement of implants. Dividing the studies based on follow-up duration, the pooled survival of implant placed simultaneously with onlay grafts after <2.5 years of follow-up was 93.1% (95% CI 82.6 to 97.4%) and after 2.5-5 years was 86% (95% CI 78.6 to 91.1%). Implant survival was found to be 85.8% (95% CI 79.6 to 90.3%) with iliac crest grafts and 95.7% (95% CI 83.9 to 93.0%) with intra-oral grafts. Our results indicated no statistically significant difference in implant survival between simultaneous and delayed placement (OR 0.43, 95% 0.07, 2.49, I 2=59.04%). Data on implant success and bone loss were limited. Data indicates that implants placed simultaneously with autogenous onlay grafts have a survival rate of 93.1% and 86% after a follow-up of <2.5 years and 2.5-5years respectively. A limited number of studies indicate no significant difference in implant survival between the simultaneous and delayed placement of implants with onlay bone grafts. There is a need for randomized controlled trials comparing simultaneous and delayed implant placement to provide robust evidence.